Production Of Taxol By Pestalotiopsis Breviseta Cr01 Isolated From The Catharanceus Roceus And Its Growth Studies. - GOWRI KARTHIK,; KATHIRAVANGOVINDARAJAN,; SUKUMARAN NATARAJAPILLAI, (International Journal of Pharma and Bio Sciences, 2012)
As there is a continuous search for the alternative source for taxol, a million dollar drug due to its scarcity scientists have chosen microorganism as one of the alternate sources.Pestalotiopsis breviseta CR01 produces taxol invitro which was isolated from the plant Catharanceus roceus. The optimum growth of this fungus was analyzed by varying different growth parameters. The presence of taxol in this fungus was confirmed through HPTLC, UV and IR spectroscopic methods. The amount of taxol was quantified through HPLC analysis. This study reveals that Pestalotiopsis brevisetaCR01 optimum growth can be attained at temperature 25°C and pH 7.5 with the presence of dextrose as carbon source.